Sales information system for sumba woven fabric with the customer relationship method - Yustina Rada; Arini Aha Pekuwali (Institute of Computer Science (IOCS), 2023)
This research is motivated by the increasing number of trading and service companies that are starting to use e-commerce systems as online sales media. In the current era of globalization and as time goes by, where the development of technology is increasingly rapid, it can be seen that the number of internet users is also increasing from year to year. In creasing product marketing and sales to consumers, it is necessary to implement a strategy to increase market share. This research aims to create and implementation Web-based marketing system for Est Sumba Ikat woven fabrics. The method used in this research is Customer Relationship Management (CRM). The results of this research show that by utilizing CRM, it will make it easier for the East Sumba Ikat Gallery to find out what is expected and needed by its customers so that closw and open business relationships will be created as well as good two-way communication. In this regard, the authors are interested in creating a loyalty system that can help the East Sumba Ikat Weaving Gallery in increasing the number of customers, increasing satisfaction and keeping customers from being tempted by various offers made by others competitors.